How to stop worrying and start living - Carnegie, Dale (Pocket New York, 1990)
Stop worrying and take the steps to a happier, more fulfilling life! Through Dale Carnegie$1 (Bs six-million-copy bestseller recently revised, millions of people have been helped to overcome the worry habit. Dale Carnegie offers a set of practical formulas you can put to work today. In our fast-paced world$1 (Bformulas that will last a lifetime! Discover how to: -Eliminate fifty percent of business worries immediately -Reduce financial worries -Avoid fatigue -Add one hour a day to your waking life -Find yourself and be yourself$1 (Bremember there is no one else on earth like you! How to Stop Worrying and Start Living deals with fundamental emotions and ideas. It is fascinating to read and easy to apply. Let it change and improve you. There$1 (Bs no need to live with worry and anxiety that keep you from enjoying a full, active and happy life!s